Predictors of willingness to accept COVID-19 vaccine among adults - Huka, Alo Edin; Alemeyehu, Lami; Jara, Dube; Ayele, Angefa; Shifa, Tofik (Frontiers in Epidemiology, 2023)
Background: Vaccines are effective and ultimate solution that can decrease the burden of Coronavirus disease-19 worldwide. However, poor knowledge and unwillingness to accept this vaccine are key barriers to manage the coronavirus disease-19 pandemic in different country including Ethiopia. The control of pandemic principal will depend on acceptance of coronavirus disease vaccine. Therefore, there is paucity of evidence on coronavirus disease vaccine acceptance in the study area. The current study was aimed to assess willingness to accept coronavirus disease-19 vaccine and associated factors among adult clients attending Bule Hora University Teaching Hospital, west Guji zone, southern Ethiopia. Methods: Institution based cross sectional study was conducted among 385 study participants which was selected by Systematic random sampling technique. Data was collected through observation and structured questionnaires from April 10 to May 30, 2022. The collected data was cleaned and entered into Epi data 3.1 software before being exported to SPSS 25 statistical software for analysis. Bi-variable and multi-variable binary logistic regression model was used to identify the predictors of coronavirus disease-19 vaccine acceptance. The strength of association was measured using AOR with 95% confidence interval and significance was declared at p-value < 0.05.Result: -Magnitude of willingness to accept coronavirus disease-19 vaccine was 67.5 % (95%Cl: 63 -72). Good knowledge (AOR= 2.07, (1.17-3.64), history of chronic disease (AOR= 2.59(1.4-4.78) government employee (AOR= 2.35(1.1-5), favorable attitude ) and good adherence (AOR=1.74(1.02-2.97) were factors that significantly associated with willingness to accept coronavirus disease-19 vaccine.Magnitude of willingness to accept coronavirus disease-19 vaccine was considerable and needs to be improved. Knowledge, attitude, chronic illness, adherence, and being government employee were factors that associated with willingness to accept coronavirus disease-19 vaccine.Community awareness, advocacy, social mobilization and health education should be given at different levels.